2021
DOI: 10.4067/s0717-75182021000300374
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de frutas, verduras y legumbres en adultos de Santiago Oriente, Chile: ¿Ha influido el confinamiento por COVID-19?

Abstract: Consumo de frutas, verduras y legumbres en adultos de Santiago Oriente, Chile: ¿Ha influido el confinamiento por COVID-19?Fruit, vegetable and legume consumption among adult residents of Eastern Santiago, Chile: Effects of the COVID-19 confinement?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
2
Order By: Relevance
“…The International Year of Pulses 2016 highlighted the importance of pulses for human health, sustainability, and, most importantly, food security. In fact, a recent study [ 1 ] aiming to compare the frequency and quantity of different types of food consumed by adults from Santiago, Chile, before and during confinement, demonstrated that the consumption frequency of legume seeds (two to four times per week) in the capital of Chile increased during the COVID-19 pandemic year from 26% (pre-pandemic period) to 33.7% (lockdown period), thus confirming the critical role of legume seeds in food security. After dry beans, chickpea ( Cicer arietinum L.) is the most important pulse [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The International Year of Pulses 2016 highlighted the importance of pulses for human health, sustainability, and, most importantly, food security. In fact, a recent study [ 1 ] aiming to compare the frequency and quantity of different types of food consumed by adults from Santiago, Chile, before and during confinement, demonstrated that the consumption frequency of legume seeds (two to four times per week) in the capital of Chile increased during the COVID-19 pandemic year from 26% (pre-pandemic period) to 33.7% (lockdown period), thus confirming the critical role of legume seeds in food security. After dry beans, chickpea ( Cicer arietinum L.) is the most important pulse [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chile es considerado un país con similitudes a los mediterráneos, por lo que la implementación de la dieta podría significar una mejora en la calidad de vida y reducción de factores de riesgo 30 . Los resultados indican que el consumo de verduras y frutas es superior al 15% reportado por la Encuesta Nacional de Salud 6 , así como el de legumbres es superior al 12% declarado en el consumo en la capital durante la pandemia 31 . Esta tendencia al aumento del consumo de alimentos más saludables durante la pandemia fue estudiada en España destacando su asociación con el aumento de la práctica de cocinar en casa 32 .…”
Section: Discussionunclassified
“…Por otro lado, Pye en el 2021 comparo la frecuencia y cantidad de consumo de frutas, verduras y legumbres, su estudio fue llevado a cabo en 1351 personas mayores de 18 años originarias de Santiago de chile, sus resultados evidenciaron que el consumo de verduras se mantuvo mientras que el de frutas disminuyo, remarcando que durante el confinamiento las personas mantuvieron un consumo insuficiente para frutas y verduras, al contrastarse con lo recomendado por las guías alimentarias (Pye, 2021). Sudria (2020) analizo el consumo alimentario durante el período de confinamiento en Argentina, a través de cuestionarios aplicados en forma online, encontró modificaciones en los hábitos alimentarios, caracterizados por descensos en el consumo de alimentos como frutas y verduras, las cuales pasan a ser los grupos de selección de estudio por excelencia, al ser considerados inmurreguladores (Sudria, 2020).…”
Section: Contingencia Generada Por Covid-19 Y Su Impacto En Habitos A...unclassified